PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PT PUTERA SRIWIJAYA MANDIRI PALEMBANG - Nelly Juniarti; Hamid Halin; Roswaty Roswaty (Universitas Indo Global Mandiri)
Purpose of this study was to determine how much influence the health and safety on the performance of employees of PT. Sriwijaya Putera Mandiri. Number of members of a population of as many as 54 employees. The sampling technique using simple random sampling and determining the sample size in this study using Slovin formula, in order to obtain the results as much as 35 respondents to be sampled in the study. This research uses descriptive analysis with quantitative approach using a questionnaire as a data collection tool and using the technique of multiple linear regression analysis to measure the influence of independent variables on the dependent variable is the safety Work (X1) and health (X2) as the independent variable (X) and employee performance as the dependent variable (Y). Processing of the data in this study aided by Stastitical program for Product and Service Solutions (SPSS) version 15. The results of this study states that occupational safety and health have a significant effect on the performance of employees of PT. Sriwijaya Putera Mandiri. Based on the results of empirical testing of safety and health variable has a value of 4.491 calculated F and the significant value of 0.001.Keywords: Occupational Health and Safety, Employee Performance